Effect of Monetary Rewards on Employees Performance in Financial Institutions: A Case Study of Pride Microfinance Kabale Branch. - Nayebare, Violah (Kabale University, 2023)
The purpose of the study was to investigate the extent to which monetary rewards affect employees' performance in micro finance institutions using pride microfinance ,kabale branch as a case study .The study was guided by the following objectives; to examine the extent to which allowances affect employees' performance in Micro finance Institutions, to establish how salaries affect employees' performance in microfinance institutions and to establish the relationship between bonuses and employees' performance in microfinance institutions. The researcher employed descriptive and analytical research designs ,thus both quantitative and qualitative data was collected with the help of questionnaires and interview guide, the data analyzed was collected for purposes of drawing conclusions and recommendations .The findings revealed that financial incentives improve on task performance because majority of the respondents supported that financial incentives improve on task performance, few of the respondents disagreed with the question while others were not sure whether financial incentives significantly improve on task performance or not. Monetary rewards make employees happy while performing their duties, majority of the respondents supported the question that monetary rewards make employees happy and satisfied while performing their duties and monetary rewards make employees perform in high degrees. A few with disagreed with the question and finally a few respondents were not sure whether monetary rewards make employees happy while performing their duties. In conclusion therefore, all objectives were achieved as set by the researcher. The nature of allowances availed to employees was found to have far reaching effects to any employee. Respondents also strongly agreed that employees were given favorable allowances at pride micro finance. There is a need to allow employees (subordinates) to make decision in some performance aspects. This would make them feel a heart of belonging thereby achieving the set goals. There is a need to continue ensuring that skilled and competent human resource management officers are employed in the organization since competent officers may be easy for employees to deal with in an effort to ensure service quality.